Chronic lower respiratory diseases among demolition and cement workers: a population-based register study. Issue 1 (11th January 2013) - Mølgaard, Ellen Fischer; Hannerz, Harald; Tüchsen, Finn; Brauer, Charlotte; Kirkeskov, Lilli
Abstract : Objective: To estimate standardised hospitalisation ratios (SHR) for chronic lower respiratory diseases among demolition and cement workers in Denmark, 1995–2009. Design: This is a population-based register study on data from 'the Occupational Hospitalisation Register'. SHR of chronic obstructive pulmonary disease (COPD) was calculated for both demolition and cement workers. Settings: Register study with data from all hospitals in Denmark. Participants: 895 demolition workers and 5633 cement and concrete workers were included in the study and all economical active men were used as reference group. Results: We found a statistically significant high SHR for the cement workers, SHR=134 (95% CI 117 to 153). The SHR for demolition workers was 131 (95% CI 87 to 188). Conclusions: We find a higher risk of being hospitalised due to COPD in cement and concrete workers (significant) and demolition workers (insignificant) compared to gainfully employed men.